2014
DOI: 10.1002/ps.3713
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric consequences of host plant occupation on the competition between the whiteflies Bemisia tabaci cryptic species MEAM1 and Trialeurodes vaporariorum (Hemiptera: Aleyrodidae)

Abstract: The interspecific interactions between B. tabaci MEAM1 and T. vaporariorum were asymmetric, with B. tabaci MEAM1 being the superior competitor. This superiority could partially explain the rapid spread of B. tabaci MEAM1 in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…tabaci and its herbivorous competitors Trichoplusia ni , Pieris rapae , Liriomyza trifolii , and Trialeurodes vaporariorum have shown that the presence of B . tabaci might influence the performance of these competitors via host plant induced defense reactions [3942]. …”
Section: Introductionmentioning
confidence: 99%
“…tabaci and its herbivorous competitors Trichoplusia ni , Pieris rapae , Liriomyza trifolii , and Trialeurodes vaporariorum have shown that the presence of B . tabaci might influence the performance of these competitors via host plant induced defense reactions [3942]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies of B . tabaci and its herbivorous competitors Trichoplusia ni , Pieris rapae , Liriomyza trifolii , and Trialeurodes vaporariorum have shown that the plants previously exposed to whitefly feeding to be less suitable for other herbivores, which subsequently showed behavioral differences (oviposition, feeding preferences) and reduced development, survival rates, and overall population growth [ 21 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…B. tabaci MEAM1 feeding induced Arabidopsis SA-signaling pathways and suppresses or does not alter the expression of JA/ethylene-regulated genes Zarate et al 2007;Zhang et al 2013b), while M. persicae infestation activates both SA-and JAsignaling pathways (Moran et al 2002;Girling et al 2008 (Zhang et al 2013a), indicating that the two species induce different defense responses in tomato. Puthoff et al (2010)'s report of these two pests feeding on tomato (S. lycopersicum) leaves inducing similar local and systemic expression patterns in several defense-and wound-response genes could perhaps be caused by a different experimental design.…”
Section: Discussionmentioning
confidence: 97%